2013
DOI: 10.1371/journal.pone.0055430
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Presence of Tissue Expanders on Energy Deposition for Post-Mastectomy Radiotherapy

Abstract: An increasing number of studies have shown that post-mastectomy radiotherapy presents benefits associated with the patients survival and a significant fraction of the treated patients makes use of tissue expanders for breast reconstruction. Some models of tissue expanders have a magnetic disk on their surface that constitutes heterogeneity in the radiation field, which can affect the dose distribution during the radiotherapy treatment. In this study, the influence of a metallic heterogeneity positioned in a br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 18 publications
2
18
0
Order By: Relevance
“…One of the limitations of this study is that we only investigated one type of the tissue expander (McGhan Style 133, ALLERGAN, Santa Barbara, CA, USA), while other brands of tissue expanders are also used for breast reconstruction,20 and only modeled the metallic port in one TPS (Pinnacle, Philips Healthcare, Fitchburg, WI, USA). However, it seems that the tissue expander used in this study was the most popular type used in the US and other countries according to literature14, 15, 16, 17, 24, 25, 31 and Pinnacle is one of the most widely used TPS worldwide, which means our model is applicable to most clinics.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the limitations of this study is that we only investigated one type of the tissue expander (McGhan Style 133, ALLERGAN, Santa Barbara, CA, USA), while other brands of tissue expanders are also used for breast reconstruction,20 and only modeled the metallic port in one TPS (Pinnacle, Philips Healthcare, Fitchburg, WI, USA). However, it seems that the tissue expander used in this study was the most popular type used in the US and other countries according to literature14, 15, 16, 17, 24, 25, 31 and Pinnacle is one of the most widely used TPS worldwide, which means our model is applicable to most clinics.…”
Section: Resultsmentioning
confidence: 99%
“…Thompson and Morgan15 manually assigned a bulk density of 7.9 g/cm 3 to the implant in TMS TPS (Nucletron, Veenendaal, the Netherlands) and concluded this kind of modeling was ineffective; Chen et al18 used a series of phantom and film measurements to find an electron density relative to water of 11.8 for the metallic port in an open field photon beam in Eclipse TPS (Varian Medical Systems, Palo Alto, CA, USA). However, this value did not yield good agreement between measurements and TPS calculations for both 6 and 18 MV photon beams; Trombetta et al20 assigned the density of the metallic port in the Eclipse TPS to be 5 g/cm 3 which is the highest available value in the system. Except for one abstract19 in which the details and accuracy of the model were not provided, none of the previous studies created and validated a model of the metallic port with generic dimensions and density that can be applied to different beam energies, neither did they investigate the impact of the metallic port on any advanced techniques like intensity‐modulated radiotherapy (IMRT) or volumetric‐modulated arc therapy (VMAT), while these techniques have been used to treat postmastectomy patients 26…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…13,16 However, a recent simulation using Eclipse planning software (Varian Medical Systems, Palo Alto, CA, USA) predicted no significant change in dose. 17 Furthermore, current treatment planning systems (TPS) are known to have limitations in calculating attenuation and heterogeneity because of the presence of very high-density objects in the path of the beam. 11 This is especially significant for surface or skin dose, at high risk of clinical relapse in the context of PMRT, so in vivo measurements are required.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Furthermore, the presence of a breast prosthesis during PMRT with photon beam is not associated with significant changes in dose distribution. 8,9 However, immediate implant-based breast reconstruction in patients requiring PMRT remains controversial because of concerns for higher risk of unfavorable reconstructive outcomes, [10][11][12] although some found that the risk of reconstructive failure after PMRT was acceptable. 13 For radiation oncologists delivering PMRT, a key question is whether specific approaches of immediate reconstruction, including implant-based reconstruction, allow for optimal coverage of the chest wall and internal mammary nodes (IMN) with acceptable doses to the heart and lungs.…”
Section: Introductionmentioning
confidence: 99%